1992
DOI: 10.2343/geochemj.26.241
|View full text |Cite
|
Sign up to set email alerts
|

The rare-earth element content of GSJ rock reference samples determined by gradient ion chromatography.

Abstract: Eleven of the rare earth elements (lanthanide series) have been determined in fifteen Geological Survey of Japan igneous reference samples by high performance ion chromatography (HPIC). Multiple analysis of each reference sample was undertaken to provide the best possible data. The technique, which employs chelating agents to permit the separation of individual rare-earth elements as anionic complexes, has a reproducibility of <4%. With the use of on-line sample solution concentration, detec tion limits of 0.1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1995
1995
2006
2006

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…Similar deviations of the ICP-MS values by Hirata et al (1988) are also plotted in Fig. Al(B (Watkins and le Roex, 1992) and the MS-ID value for Ho using 163Ho with T112 = 6,000 y (Kawakami and Masuda, 1984) were tentatively used as the reference values. For the Tm data, however, we did not make such cal culations, since we cannot select any acceptable Tm value for JB-1 except for our ICP-AES value and the ICP-MS one by Hirata et al (1988).…”
Section: Appendixmentioning
confidence: 82%
See 2 more Smart Citations
“…Similar deviations of the ICP-MS values by Hirata et al (1988) are also plotted in Fig. Al(B (Watkins and le Roex, 1992) and the MS-ID value for Ho using 163Ho with T112 = 6,000 y (Kawakami and Masuda, 1984) were tentatively used as the reference values. For the Tm data, however, we did not make such cal culations, since we cannot select any acceptable Tm value for JB-1 except for our ICP-AES value and the ICP-MS one by Hirata et al (1988).…”
Section: Appendixmentioning
confidence: 82%
“…In this context, the HPIC technique (le Roex and Watkins, 1990;Watkins and le Roex, 1992) is not satisfac tory, since Ho, Tm, and Lu data are not reported by their HPIC method due to analytical difficulties caused by the co-elution of Y with Ho and detec tion limits for Tm and Lu. ICP-MS is currently one of the most sensitive techniques to analyze all REE.…”
Section: Appendixmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the pretreatment of sample using an ion-exchange column is generally carried out in the HPIC/HPLC analysis (Cassidy, 1988;le Roex and Watkins, 1990;Watkins and le Roex, 1992;Asahara et al, 1995;Na et al, 1995). The procedure of matrix removal used in this study is the modified version of the method described in Lee et al (2000).…”
Section: Sample Dissolution and Matrix Removalmentioning
confidence: 99%
“…The instruments of HPIC/HPLC are currently used in widespread analytical routines in institutes globally, and commercially available at a reasonable cost. Some pioneering studies revealed that the HPIC/HPLC is an excellent means of REE analysis in rock samples (Cassidy, 1988;le Roex and Watkins, 1990;Watkins and le Roex, 1992;Asahara et al, 1995;Na et al, 1995), although some REE (Dy or Ho in all cases and Er, Tm and Lu in individual cases) were not measurable and relatively large sample size (300 to 1000 mg) was generally required in these studies for precise REE analysis. In this paper, we present an improved HPIC technique in which all fourteen REE in rock samples as small as <50 mg can be determined with satisfactory precision and accuracy.…”
Section: Introductionmentioning
confidence: 99%